Realization of the right to protection against illegal intervention into personal life in the principles of credit information - Misko, Maxim V. (Journal of the Belarusian State University. Law, 2019)
The article discusses the issues of credit information in the context of the observance of the constitutional rights of man and citizen. The importance of credit bureaus for the economy, the banking system, lenders and borrowers is emphasized. It justifies the expediency of balancing private and public interests in the process of creating a credit reporting system. Based on the analysis of the principles of credit information, the author formulates proposals for making changes and amendments to the legislation of the Republic of Belarus.
Keywords: credit history; credit information; principles; Credit register; credit